Relationship between Performance Appraisal and Employee Performance in Level Four Hospitals in Kisii County, Kenya - Omweno, Lilian Nyaboke; Juma, Dennis (Human Resource and Leadership Journal, 2025)
Purpose: The study sought to investigate the relationship between performance appraisal and employee performance in level 4 hospitals in Kisii County. Methodology: The research adopted a descriptive research design. The study target populations of this study was staff of level four hospitals in Kisii County while the study population was 1200 employees. The study adopted stratified sampling and Yamane formula to get 300 respondents. The researcher used questionnaires as the main data collection instrument. Findings: The findings revealed that performance appraisal planning, methods, goals and feedback had a positive and significant influence on employee performance in level 4 hospitals in Kisii County (β=0.253; p = 0.008; β=0.230; p = 0.008; β=0.272; p = 0.003; β=0.304; p = 0.001 respectively). Unique Contribution to Theory, Policy and Practice: The level four hospital administration through their human resource departments should devise new performance appraisals that factor in best practice and best criteria fit that are canvassed and agreed to by majority of employees. The level four hospital administration should ensure that employees receive consistent feedback, preferably within a month after filling in their performance appraisal forms. Performance appraisal should be transparent, timely and effective for employees.